The Role Of My Qiraah Application To Improve The Ability To Read The Qur’an Students At Muhammadiyah University Of Yogyakarta - Ariandi, Ariandi; Fauzan, Aris (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The Al-Qur'an is Kalamullah, which requires careful attention to the rules of Tajwid science when reading it to avoid misunderstandings. Muhammadiyah University of Yogyakarta is one of the Islamic tertiary institutions that requires every student to have a certificate for the Al-Qur'an Reading and Writing program as a graduation requirement. The purpose of this research article is to reveal the history and role of My Qiraah application as a support for students' Al-Qur'an learning activities at Muhammadiyah University of Yogyakarta. The method used in this research is descriptive analytics with a qualitative approach. This method serves to describe an object under study. It begins with observing the Al-Qur'an Reading Guidance activities, followed by collecting data through interviews with primary sources and analyzing the data obtained by strengthening secondary sources. The results of this study indicate that My Qiraah is an application for learning the Qur'an, which was adopted from the 10-hour Al-Qur'an learning method by Muhammad Chirzin. My Qiraah application was implemented in the 2021-2022 school year, and improvements are still being made to continue supporting Al-Qur'an learning activities for students at UMY. The presence of My Qiraah application dramatically helps in the learning process of Al-Qur'an Reading Guidance for the Muhammadiyah University of Yogyakarta students. This is evidenced by a 3.3% increase in student BTA graduation in the 2022/2023 school year.